(untitled) (Transactions of the Association of European Schools of Planning, 2020)
By definition sovereign, States find themselves inescapably in a situation of permanent competition. Moreover, given that an inherent quality of sovereignty is to exclude obeying whomever else, nobody, neither individuals nor institutions can arbitrate between them. This being the case, in the international arena power becomes the one and only currency. It seems basic even to each State’s survival: in this endless competition, the sustainability of each depends on the capacity to maintain a sufficient level of power. (Badie, 2018, p.44 translated by the author) What is ... needed is reflecting on new ways of adapting politics and democracy to the unique and universal world of networks... (Balligand and Maquart, 1990, p.219 translated by the author) The above quotes relate to the ambivalence of its members towards the European Union construct. Wishing to remain sovereign, they simultaneously acknowledge that they have to adapt to a new world. So, they conclude treaties which give the Union specific powers. Unable to unilaterally give itself powers, or ‘competences’ in EU jargon, their Union is therefore ‘intergovernmental’. If it were able to assume powers on its own, it would be like a federal state. As such, the Union could exercise some degree of ‘territoriality’, or control over its borders. As it is, it cannot.